Case Study: Program Fisioterapi pada Kasus Penyakit Paru Obstruktif Kronis (PPOK) - Igildafani Moutya Devi; Agus Widodo (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: COPD is a major cause of morbidity and mortality globally. COPD is a disease characterized by continuous and progressive airflow limitation, accompanied by coughing and increased sputum production. Objective: To determine the effect of nebulizer, pursed-lip breathing, and deep breathing on the degree of shortness of breath, expansion of the thorax cage, and functional capacity in COPD patients. Methods: This research method was carried out directly on one respondent with a COPD case by presenting therapy for 3 therapy sessions. Measurement of the degree of shortness of breath using the Modified Borg Dyspnea Scale and the Modified Medical Research Council (mMRC) Dyspnea Scale, expansion of the thorax cage using metline, and functional capacity using 6MWT. Results: After 3 times therapy, the Borg Scale results from 4 to 2 and mMRC from 4 to 2, the expansion of the thorax cage at the axilla point from 3 cm to 4 cm and the Xyphoid process point from 4 cm to 4.5 cm, and capacity functional from 2,365 METs to 2,674 METs. Conclusion: The use of nebulizer, pursed-lip breathing (PLB), and deep breathing can reduce shortness of breath, increase the expansion of the thorax cage, and improve functional ability in COPD patients.Keywords: COPD, breathing exercise, dyspnea, expansion of thoracic cage, functional capacity